Power and poverty Development and development projects in the third world - "Attwood , Donald W (ed.)" (London, 1988)
This book presents case studies concerning the impact of development projects on societies at various levels of affluence and modernization. They demonstrate project variety, and the ecological, economic, political and social contexts within which development is attempted but seldom achieved.
Keywords: Power-Poverty